Mucopyocele of concha bullosa mimicking ethmoidal polyp (Bangladesh Journal of Medical Science, 2018)
Concha bullosa (CB) is a pneumatised middle turbinate. Although CB is the most common variant of the middle turbinate, the formation of mucocele or mucopyocele of CB has been rarely reported. The inflamed mucosal lining of the concha bullosa may lead to mucocele formation. Infection of the retained secretion will later on lead to mucopyocele. We report a 12-year-old girl presented with right unilateral nasal blockage associated with rhinitis symptoms. She was initially diagnosed as nasal polyp which later on turned out to be a mucocele histpathologically.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.691-693